Wybrane problemy wykonywania kary sekwencyjnej - Raglewska, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
This paper concerns the sequence of punishments: imprisonment and restriction of liberty on the basis of Article 37b of the Criminal Code. The article presents the problems related to the execution of sequential penalties. The author considers the possibility of modifying the sequence of penalties, e.g. in the form of execution of a penalty in the electronic supervision system. The considerations were supplemented with own research.
Keywords: mixed punishment; sequence of punishments; electronic surveillance system; incidental proceedings